Clontuskert Augustinian Priory, rood screen, arch - O'Donovan, Danielle (My University, 2008)
Arches of rood screen, moulding from soffit comprises: quadrant, fillet, quarter-hollow, fillet, right-angled rebate, fillet, ogee, right-angled rebate, ogee, fillet, hollow chamfer, quadrant, ogee, fillet. Extensive use of ogees here, a late Gothic moulding rarely found in Ireland. When found it is often in association with very high quality work.
Rood screen
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Augustinian; Late Medieval; moldings, hollow; fillets (moldings); moldings, ogee; roll moldings